The Future of Higher Vocational Education Ecosystem in Shanxi Province, China - Meng, Wanrong; Tuntinakhongul, Ampapan (My University, 2023)
The aim of this study is to investigate the prospects of Shanxi's higher vocational education ecosystem. We conducted a collaborative study with 17 experts from Shanxi, China, using the Delphi technique to analyse the future development trends of higher vocational education in education administration. All experts were given a survey questionnaire consisting of 51 items. These projects are situated within the key dimensions of the Shanxi higher vocational education ecosystem. The seven dimensions are further categorised into the internal and external environments. The internal environment of an educational institution consists of students, teachers, management personnel, and other technical staff. The external environment encompasses various aspects, including politics, society, and the economy. The recommendations provided by these experts will have an impact on the policy-making process for the future development of higher vocational education in Shanxi Province.
Keywords: China; Higher vocational education ecosystem; Shanxi province; The Delphi technique; The future